The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/app.22884
|View full text |Cite
|
Sign up to set email alerts
|

Performance of natural‐fiber–plastic composites under stress for outdoor applications: Effect of moisture, temperature, and ultraviolet light exposure

Abstract: ABSTRACT:The effects of moisture, temperature, and ultraviolet (UV) light on performance of natural-fiber-plastic composites (NFPC) were assessed. We conducted short-term tests in the laboratory and long-term tests under natural exposure and measured changes in mechanical properties and color in samples of the composite. Chemical changes of the composite's materials were measured by X-ray photoelectron spectroscopy to elucidate the mechanisms of chemical transformations on the material surface. Relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 11 publications
2
38
1
Order By: Relevance
“…This might be because of the lower degree of crystallinity of OPS nanoparticles which leaded to higher water absorption of the sample. The reduced degree of water absorption due to the replacement of the hydroxyl groups with carbon atoms in the PF chains has also been reported by several researchers (Lopez et al 2006; Abdul Khalil et al 2010b). Abdul Khalil et al (2010b) found an interesting result that the highest water absorption because of the presence of more hydroxyl groups in the parenchyma tissue that enabled more hydrogen bonding formation.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This might be because of the lower degree of crystallinity of OPS nanoparticles which leaded to higher water absorption of the sample. The reduced degree of water absorption due to the replacement of the hydroxyl groups with carbon atoms in the PF chains has also been reported by several researchers (Lopez et al 2006; Abdul Khalil et al 2010b). Abdul Khalil et al (2010b) found an interesting result that the highest water absorption because of the presence of more hydroxyl groups in the parenchyma tissue that enabled more hydrogen bonding formation.…”
Section: Resultssupporting
confidence: 67%
“…It was found that long-term exposed of the composites to elevated conditions affected the mechanical properties. Solar irradiance (UV component of the sunlight), relative humidity and temperature are the causal agents of this deterioration of natural fiber of impregnated samples (Lopez et al 2006). The increase in the mechanical properties due to the chemical modification has been reported by several researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have reported that inclusion of maleated olefins with the composite blend considerably reduces water absorption when using bio-fillers such as poplar wood, loblolly pine wood, sisal fiber, or wheat straw. [34][35][36][37][38] Particle size of PW in composite blends did influence weight gain (Figure 4). Composite blends composed of smaller particles (PP-#200PW-MAPP and PP-25BGPW-MAPP) exhibited less weight gain than composites that contained larger particles (PP-#40PW-MAPP and PP-#60PW-MAPP) (Figure 4).…”
Section: Influence Of Mixing Different Fillersmentioning
confidence: 99%
“…Environmental stresses such as water soaking may cause changes in the mechanical properties to occur, which needs to be measured in order to assess the potential commercial value of a composite (Thwe and Liao 2002;Lopez et al 2006;Clemons and Stark 2009;Zabihzadeh 2010). For example, flexural properties have been reported to decrease when lignocellulosic plastic composites are weathered (Thwe and Liao 2002;Lopez et al 2006;Clemons and Stark 2009).…”
Section: Water Absorption Responsesmentioning
confidence: 99%
“…For example, flexural properties have been reported to decrease when lignocellulosic plastic composites are weathered (Thwe and Liao 2002;Lopez et al 2006;Clemons and Stark 2009). In this work, the Type V tensile bars that were not soaked and Type V bars that were soaked in water for 672 h were tested for their mechanical properties, as shown in Table 4.…”
Section: Water Absorption Responsesmentioning
confidence: 99%